International Research Funding in African Higher Education`: Risks and Benefits - Ransom Tanyu, Ngenge (International Higher Education, 2025)
<h3 id="despite-contradictory-evidence-from-university-rankings-such-as-qs-and-the-times-higher-education-world-university-rankings-the-impact-of-external-research-funding-on-african-higher-education-remains-an-open-question-while-external-funding-provides-critical-financial-resources-it-usually-has-conditionalities-that-may-undermine-the-autonomy-and-sustainability-of-african-higher-education-this-article-dissects-its-benefits-and-risks-with-case-studies-from-kenya-uganda-and-south-africa-and-proposes-balanced-funding-strategies" data-pm-slice="1 1 []">Despite contradictory evidence from university rankings such as QS and The Times Higher Education World University Rankings, the impact of external research funding on African higher education remains an open question. While external funding provides critical financial resources, it usually has conditionalities that may undermine the autonomy and sustainability of African higher education. This article dissects its benefits and risks, with case studies from Kenya, Uganda, and South Africa, and proposes balanced funding strategies.